Easiness of Image Interpretation of Spot XS and Landsat TM for Urban Land Cover Object Identification - Agus Suryantoro (Universitas Muhammadiyah Surakarta, 2003)
The study that has been out for URGE project “Remote sensing for urban study and landuse planning” is a especially the possibility and the easiness of interpretability. The easiness of interpretation of satellite image is influenced by sensor, and the physical condition of urban area. SPOT image recorded in 1996 and TM Landsat image recorded in 1994 by the process of digital image are used as the comparison of easiness of interpretation. The contras sharpening method using a filter, the arrangement of composite image, and multispectral classification is applied by respective image. The introduction of covered object of urban area is based on the introduction of spatial and spectral pattern. Visual and digital interpretation that based on multispectral classification has been done to get the accurateness of classification result. The result of this study shows that SPOT image has better detail information than TM Lansat image. But the spectral information of TM Lansat image has more varieties than that of SPOT image so that certain objects, especially straight appearance (street, river, etc) can be know more by TM Lansat.